PLN CSR Program Through Community Empowerment at Saguling Dam, Citarum River, Bandung, West Java - Gan Gan Giantika; Siti Qona’ah (Golden Ratio of Data in Summary, 2024)
Saguling Dam is a man-made reservoir located in West Bandung Regency, which dams the flow of the Citarum River, the largest river in West Java. The current condition of the dam has been heavily polluted by an abundance of water hyacinth and a buildup of household waste covering the river's surface. According to data from the Bandung City Sanitation Company in 2016, approximately 2.5 million residents produced 1,500 - 1,600 tons of waste per day. However, only 1,100 - 1,200 tons were transported to the Sarimukti Final Disposal Site (TPA), and 150 - 250 tons were processed by residents. The remaining 150 - 250 tons of waste were disposed of in Citarum River's tributaries. PLN (State Electricity Company) implemented a Corporate Social Responsibility (CSR) program themed "Green Employee Involvement" through community empowerment efforts aimed at addressing the waste problems in the Saguling Dam. The "Green Employee Involvement" program, in collaboration with the Bening Saguling Foundation, was carried out in celebration of World Environment Day 2024. The research methodology used is qualitative, employing a case study approach. Data collection methods include literature review and observation. The research findings show that PLN's Corporate Social Responsibility program, themed "Green Employee Involvement" in collaboration with the Bening Saguling Foundation, has had a positive impact on environmental preservation while also providing economic benefits to the community in the Saguling Dam area, Bandung, West Java.